Explanatory analysis of graduates’ creative capacity, market orientation and entreprenuership intention in Southwestern Nigeria (2022)
The study assessed the explanatory analysis of graduate entrepreneurship intention, creative capacity, and market orientation in southwestern Nigeria. The study adopted descriptive research design of the correlational type while multi-stage sampling procedure was adopted. The six states (LGAs) were enumerated while simple random sampling technique was used to select three states namely Lagos, Osun, and Ekiti States. Also, simple random sampling technique was used to select 2,000 graduates from the list officially obtained from government education agencies. Through, app-enabled survey, Survey Heart was used to deployed instruments used namely: Entrepreneurship Intention (r= 0.72); Graduate Creative Ability Scale (r=0.77) and Market orientation Scale (r=0.89). All the three instruments were placed on a rating range of extreme low (1) to Very high (5). The quantitative data were analysed using descriptive statistics and Pearson product moment correlation at 0.05 level of significance. The findings of the study revealed the levels and significant relationships of the two independent variables to graduate entrepreneurial intention in southwestern Nigeria. The implication of the findings and recommendations were made accordingly.